2017
DOI: 10.1016/j.jda.2016.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Burrows–Wheeler transform and LCP array construction in constant space

Abstract: In this article we extend the elegant in-place Burrows-Wheeler transform (BWT) algorithm proposed by Crochemore et al. (Crochemore et al., 2015). Our extension is twofold: we first show how to compute simultaneously the longest common prefix (LCP) array as well as the BWT, using constant additional space; we then show how to build the LCP array directly in compressed representation using Elias coding, still using constant additional space and with no asymptotic slowdown. Furthermore, we provide a time/space tr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…Finally, Crochemore et al [23] showed how to transform a text into its Burrows-Wheeler transform by using O(lg n) of additional bits. Due to da Louza et al [24], this algorithm was extended to compute simultaneously the longest common prefix (LCP) array [21] with O(lg n) bits of additional working space.…”
Section: Related Workmentioning
confidence: 99%
“…Finally, Crochemore et al [23] showed how to transform a text into its Burrows-Wheeler transform by using O(lg n) of additional bits. Due to da Louza et al [24], this algorithm was extended to compute simultaneously the longest common prefix (LCP) array [21] with O(lg n) bits of additional working space.…”
Section: Related Workmentioning
confidence: 99%
“…The BWT has been subject of intense research in the last two decades, from compression [11,16,17,29], algorithmic [9,24,30], and combinatorial [10,13,32] points of view (mentioning just a tiny selection from the recent literature). It has also been extended in several ways.…”
Section: Related Workmentioning
confidence: 99%

When a Dollar Makes a BWT

Giuliani,
Lipták,
Masillo
et al. 2019
Preprint
“…We presented an algorithm that computes the BWT in-place together with the LCP array in quadratic time using constant workspace [Louza and Telles 2015]. We also introduced the first algorithm to compute the LCP array directly in a compressed representation [Louza et al 2017a].…”
Section: Bwt and Lcp Construction In Constant Spacementioning
confidence: 99%